IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 66 TAHUN 2010 TERHADAP PEMBERDAYAAN DEWAN PENDIDIKAN DAN KOMITE SEKOLAH - Arif Suryono; Rahmad Santosa; Haryadi Haryadi (Jurnal Dinamika Hukum, 2013)
Arief Suryono, Rahmad Santosa, dan HaryadiUniversitas Jenderal Soedirman PurwokertoE-mail:The paradigm of education, has actually brought a major change in educational policy-making at the local level as well as the school, including implementation Goverment Regulations No. 66 Year 2010. This research aims to know the implementation government regulation Goverment Regulations No. 66 Year 2010 of the empowerment board education and the school committee.The study was conducted in 18 provinces. Method of data collection using questionnaires and in-depth interviews, while data analysis is done using a simple statistik (quasi statistics), the cross-tabulation and percentages. The results show on implementation government regulation No 66 year 2010, board of education, department of education, school committee, principals and teachers need more constructive communication, and it’s can happen by clearly partnership, employment patterns and authority. The functions and duties of the school committee only on preparation and adoption of new RAPBS and school committee with the school system didn’t have a clear working partnership with it. Board of education and the school committee also didn’t have a definite budget, this difficult to recruit human resources who have qualified in the field of education, which can improve the best performance of the board of education and school committees.Keywords:   board of education, school committes, school system